Opening statement: XIII internation, AIDS conference durban, south Africa 9th July, 2000 - Piot, Peter (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Mr President, His Majesty King Zwelithini, Professor Coovadia, Nkosi, friends... good evening. We have come to Durban to break the silence - To break the silence, stigma, indifference and ignorance surrounding the Aids epidemie. At the outset, I pay tribute to those who marcbed this afternoon, to break the silence around treatment and care for people living with HIV. I have attended all International Aids Conferences since 1985. BuL this one feels different to me. Because this is the First international conference in the south - in Africa. Finally. Today, there is new hope - we are seeing an unprecedented increase in political commitment and resources to fight the epidemie. And 1 wholeheartedly applaud President Mbeki’s, powerful voice here tonight. [...]